Communication and Change - Katz, James E.; Zhou, Baohua; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Communication and Change (C&C) is a peer-reviewed, open-access, international journal that is dedicated to advancing the understanding of communication in the context of rapid technological and societal transformation. We recognize the profound impact of emerging technologies such as artificial intelligence (AI) and big data on communication practices, social structures, and media landscapes. Our mission is to foster innovative research and theorizing that examines the interplay between communication and change, with a particular focus on the following fundamental areas: Emerging Technologies and Communication: Our major focus is on how emerging technologies affect communication practices, redefine human communication and human-machine interaction, influence journalism, and drive the political economy of information. We also emphasize the importance of addressing ethical considerations in the development and use of these technologies. Communication as a Catalyst for Change: We believe that communication is not merely a reflection of societal change but a powerful force that can both exacerbate and moderate conflict, foster understanding and empathy, or fuel division, misinformation, and devastation. We aim to publish papers that unravel the complexities of communication in an era of unprecedented global connectivity and that dissect problems as well as explore potential drivers of positive social change for all sectors of society. Advancing Communication Theory and Research: We encourage theoretically grounded empirical research from a variety of perspectives that examine the intellectual and practical implications of communication and change. We are committed to publishing high-quality scholarship that engages with the special conundrums presented by the digital era. New Perspectives for New Communication Technologies: We strive to develop novel theoretical frameworks and adapt existing ones to better understand the unprecedented landscape of the ongoing technological revolution. We explore how new media (re)construct communication behaviors, social interactions, and individual relationships. We expect our contributors to leverage original research methods to generate deeper insights into these phenomena. Leading the Discourse on Communication: We aspire to be at the forefront of intellectual discourse on the evolving nature of communication, serving as a preeminent platform for innovative research from around the globe. We are especially interested in amplifying thoughtful and insightful voices of communication researchers from regions that are not already well-served by communication journals. In this way, we aim to foster a rich, vibrant community of scholars dedicated to understanding relationships between communication, technology, and social change. By publishing cutting-edge research, promoting interdisciplinary dialogue, and engaging with an array of perspectives, we aim to deepen intellectual understanding of communication practices, inform policy development, and promote cross-cultural insight. Ultimately, C&C will ardently pursue growth in disciplinary knowledge that will be in service to a more informed, connected, and prosperous world.
Keywords: Communication; Digital media; Journalism; Media and Communication; Digital and New Media; Multimedia Journalism